2015
DOI: 10.1007/s12026-015-8670-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor

Abstract: Connective tissue growth factor (CTGF), a CCN family member, is a secreted protein regulating cellular functions, including fibrosis, apoptosis, adhesion, migration, differentiation, proliferation, angiogenesis, and chondrogenesis. CTGF increases proinflammatory factor production; however, inflammatory cytokine regulation by CTGF is poorly understood. The aim of this study was to identify novel biological functions and elucidate the functional mechanisms of CTGF. Specifically, the study focused on the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Lin et al have shown that CTGF regulates CXCL8 promoter via NF-κB signaling. 38 As CTGF and CXCL8 were concomitantly downregulated by vemurafenib and trametinib, we assumed that CTGF might contribute to increased CXCL8 expression also in melanoma. However, our results revealed that CTGF neither influenced CXCL8 expression nor NF-κB activity in melanoma cells.…”
Section: Discussionmentioning
confidence: 95%
“…Lin et al have shown that CTGF regulates CXCL8 promoter via NF-κB signaling. 38 As CTGF and CXCL8 were concomitantly downregulated by vemurafenib and trametinib, we assumed that CTGF might contribute to increased CXCL8 expression also in melanoma. However, our results revealed that CTGF neither influenced CXCL8 expression nor NF-κB activity in melanoma cells.…”
Section: Discussionmentioning
confidence: 95%
“…As a limitation, we could not show direct evidence that IL-1β induced the binding of NF-κB and AP-1 to the IL-36γ promoter region. So, possible contribution of other mechanisms, such as MAPKs-mediated post-transcriptional mechanism reported in IL-8 mRNA expression [ 34 ], should be investigated in the future. Taken together, it was suggested that NF-κB and AP-1 play a critical role in IL-1β-induced IL-36γ expression in colonic myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a higher expression of CTGF has been also shown in diabetes [ 30 ]. CTGF is strongly up-regulated in disorders, frequently developed by diabetic patients, like cardiovascular disease, nephropathy, neuropathy, and retinopathy [ 36 ]. In line with this, CTGF has been reported as strongly expressed in glomeruli of diabetic patients and animals with nephropathy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%